A rapid review of factors influencing food decisions among economically disadvantaged families. (20th October 2021) - Ravikumar, D; Spyreli, E; Woodside, J; McKinley, M; Kelly, C
Abstract: Introduction: The importance of external and household family food environments in establishing healthy eating habits during childhood is well reported. Deprived areas are at a nutritional disadvantage due to the high prevalence of fast food outlets and convenience stores. Little is known about the impact of food environments on food-related behaviours of low-income families. This rapid review aimed to synthesise available qualitative evidence on parental perspectives of environmental factors that influence food planning, purchasing and processing among economically disadvantaged families with children. Methods: This review included qualitative and mixed-methods studies published after 2000 from Europe, North America and Oceania. Search strategies included seven concepts: family, food, perceptions, influences, environment, socio-economic status and study type. Thematic synthesis was employed. Results: Fourteen articles from the USA, Australia and the UK remained following screening by two reviewers. All parents had a desire to provide healthy food for their children, but they were impeded by child food preferences and beliefs about food behaviours and nutrition. In the external environment, food outlets/availability, cost and marketing influenced food choices amongst parents. Social determinants had a dominant negative influence on food decisions, including hectic daily schedules and time constraints and most importantly limited finances. Social support and support from nutrition programmes and cooking interventions had a positive influence on family food decisions. Conclusions: This synthesis of qualitative evidence highlights the challenges and opportunities that low-income parents face to feed their families. Improvements in parental food choices and feeding behaviours can only be improved if inequities in health, such as access to affordable healthy food, are addressed. Key messages: This review concluded that income, time constraints, food cost and limited food availability/outlets can have a negative effect on family food decisions. Social supports such as cooking programmes play a positive role in ensuring healthy food options for families.